Dialectics of Educational Counseling Development - Elihami Elihami (Sublim: Jurnal Pendidikan, 2022)
The essay gives a theoretical analysis with the aim of considering conflict resolution in educational orientation practice. The dialectic theory of mediation, which we believe offers a wide range of opportunities for the development of skills and social abilities as well as changes to the educational practices of professionals working in this field, is the theoretical perspective that is primarily highlighted. The relatively limited number of outputs that address the topic, including articles, dissertations, and theses, justifies the theoretical review. We first strive to study the significance of the ideas of mediation and conflict, highlighting historical features and major conceptions, to then draw on the extensive experience of one of the article's authors to discuss the role of these professionals on the management and mediation of conflicts.